Antimicrobial effect and kinetic inhibition of partially purified extracellular protease of Shigella dysenteriae by the volatile oils of Camellia sinensis - Folorunso Olufemi Samuel; Adeola Segun; Marycelin Mandu Baba; Jill Farrant (International Journal of Phytomedicine, 2013)
In spite of great advances observed in modern medicine, plants still constitute a major source of medicine especially in developing countries. Hence, there is need for unrelenting effort in the exploration of the health benefit of medicinal plants. This work was designed to determine the effect of the volatile oils of Camellia sinensis on the extracellular protease, which is one of the major virulent factors in the pathogenesis of Shigella dysenteriae and its antibacterial effects on eight other enteric bacterial as compared with the antibiotics. The average total growth inhibition of the volatile oils from the leaf, stem and root of Camellia sinensis (291.0±33.0 mm) was significantly higher (p>0.05) than the antibiotics tested (97.0±25.0 mm). The minimum inhibitory and bactericidal concentrations of the oils revealed Escherichia coli as the most sensitive organism. However, relatively higher concentrations of the oils are required to achieve similar sensitivity against Salmonella and Shigella species. The kinetics of partially purified extracellular protease, which is one of the adjuncts virulence factors of Shigella dysenteriae, was competitively (leaf and root) and noncompetitively (stem) inhibited by these oils from different parts of the plant. The activity of this enzyme increased steadily between pH 7.0 – 8.0 and 40 – 50 oC. The volatile oils possessed antimicrobial activity and showed both competitive and noncompetitive kinetic inhibition of the extracellular protease of Shigella dysenteriae. The inhibitory action of the oil on extracellular protease from Shigella dysenteriae suggests the possible mode of action. Volatile oil from Camellia sinensis, especially the leaf, may be an important source of antibiotic against these organisms particularly Shigella dysenteriae.